Preoperative Maxillary Sinus Imaging and the Outcome of Sinus Floor Augmentation and Dental Implants in Asymptomatic Patients. (March 2020) - Ritter, Amit; Rozendorn, Noa; Avishai, Gal; Rosenfeld, Eli; Koren, Ilan; Soudry, Ethan
Objectives: Preoperative maxillary sinus imaging findings have been suggested to be associated with complications and outcomes of sinus lift and dental implant procedures; nonetheless the evidence is controversial. The aim of this study was to examine the association between preoperative maxillary sinus imaging findings and outcomes of sinus lift and dental implant procedures in asymptomatic patients. Methods: We included all patients who underwent maxillary sinus lift and dental implant procedures between 2014 and 2017. Maxillary sinus imaging findings were extracted from pre-procedural dental computed tomography scans, and outcomes of the procedures were assessed. Results: A total of 145 procedures were included. No sinonasal symptoms were reported preoperatively. In 46% of cases maxillary sinus imaging was abnormal. The most common imaging finding was peripheral mucosal thickening (38%). Sinus floor cyst/polyp was identified in 13% of the cases, of which 47% occupied more than 50% of the sinus volume. Partial or complete opacification of the maxillary sinus was documented in 3% of cases. The sinus ostium and ostiomeatal complex were obstructed in 7% and 1%, respectively. Mucosal perforation was documented in 22% of cases and was inversely related to mucosal thickening ( P = 0.011). Other minor post-operative complications did not correlate with radiological findings. Post-surgical sinusitis was not observed in any of the patients regardless of pre-surgical imaging findings. Conclusions: Incidental maxillary sinus imaging findings such as mucosal swelling, cysts or polyps, regardless of their severity or size, and maxillary ostial obstruction may not need to be addressed prior to sinus augmentation and dental implant procedures in asymptomatic patients. Patients with complete sinus opacification should be referred to an otolaryngologist prior to surgery. Further controlled trials, in larger cohorts, are needed to corroborate our findings.